Prevalence of positive reactions in intradermal and IgE serological allergy tests in dogs from South Australia, and the subsequent outcome of allergen‐specific immunotherapy. Issue 1 (19th November 2019) - Han, C; Chan, WY; Hill, PB
Abstract : Objective: To determine the prevalence of positive allergen reactions in intradermal and IgE serological tests in dogs presenting to a dermatology referral centre in South Australia and the clinical efficacy of subsequent allergen‐specific immunotherapy. Design: Retrospective study. Methods: Results from 108 intradermal allergy tests, 25 IgE serological assays and immunotherapy outcomes in 37 dogs were retrospectively analysed. Immunotherapy outcomes were determined as excellent, good, modest or failure using a global assessment of efficacy matrix which incorporated pruritus scores, lesion severity, medication requirements, and owner and clinician opinion. Results: The most common positive reactions in intradermal allergy tests were Red clover (59%), Dermatophagoides farinae (29%), Tyrophagus putrescentiae (28%), Yellow dock (25%) and Malassezia pachydermatis (24%). In the IgE serological tests, Yorkshire fog grass (40%), Yellow dock (36%), Kentucky bluegrass (36%) and T. putrescentiae (36%) were the most commonly reported positive results. The outcome of allergen‐specific immunotherapy was judged to be excellent in 20% of dogs, good in 15%, modest in 18% and a failure in 47%. Conclusion: As has been reported in other geographical areas, environmental mites and plant pollens frequently gave positive reactions in allergy tests in South Australia. However, the prevalence of individual allergen reactions differed between intradermal and IgE serological tests, with M. pachydermatis being identified as a common cause of hypersensitivity in intradermal tests but not in IgE serological assays. Immunotherapy was judged to be a beneficial treatment in 35% of dogs but was essentially unsuccessful in 65%.